(untitled) (Zoological Records and Reviews, 2023)
Freshwater lakes represent biodiversity hotspots that support a disproportionately high fraction of global freshwater species within a limited spatial extent. The inland lakes and reservoirs of the Deccan Plateau, while individually modest in size compared to the African Great Lakes or Himalayan glacial lakes, collectively represent an ecologically significant freshwater network supporting diverse animal communities including fish, aquatic macroinvertebrates, waterbirds, amphibians, and aquatic reptiles. This study presents a comprehensive assessment of animal biodiversity patterns across 42 freshwater lakes and reservoirs spanning a gradient of size, trophic state, and human disturbance in Andhra Pradesh and Telangana, India, surveyed using standardised fish sampling, macroinvertebrate protocols, waterbird point counts, and herpetofauna transects over two annual cycles (2021-2023). A total of 384 animal species from five groups are documented. Fish (108 species) and waterbirds (148 species) contributed the highest richness. Lake area, macrophyte cover, and trophic state (total phosphorus) are the three strongest predictors of total animal species richness. Hypertrophic urban lakes support fewer than 30% of the species richness of oligotrophic rural reservoirs. Eight fish species are new records for Telangana and Andhra Pradesh. Twelve species are IUCN Threatened. The results identify priority lakes for conservation investment and provide a baseline for long-term freshwater biodiversity monitoring in the Deccan Plateau.